Analysis of high resolution ro-vibrational spectrum of the CH2=CHD molecule in the region of 2800 - 3300 cm−1 : the v2+ v3, v2+ v12, v1, v5, v7+ v11 and v9 bands - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Zhdanovich S. A. Stanislav Andreevich; Tan T. L.; Gabona M. G. (Poster Session F, 2015)
Title screen